2012
DOI: 10.1039/c1cc14275e
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin based porous organic polymers: novel synthetic strategy and exceptionally high CO2adsorption capacity

Abstract: Iron containing porous organic polymers (Fe-POPs) have been synthesized by a facile one-pot bottom-up approach to porphyrin chemistry by an extended aromatic substitution reaction between pyrrole and aromatic dialdehydes in the presence of small amount of Fe(III). The Fe-POPs possess very high BET surface area, large micropores and showed excellent CO(2) capture (~19 wt%) at 273 K/1 bar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
166
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(170 citation statements)
references
References 34 publications
3
166
0
1
Order By: Relevance
“…Up to now, different types of adsorbents have been used in CO 2 PSA, such as zeolites, activated carbons, silica gel, metal-organic frameworks (MOFs), and porous organic polymers [10][11][12][13][14][15]. Activated carbons generally have higher CO 2 adsorption capacity than zeolite-like materials at pressures greater than atmospheric pressure due to surface hydrophobicity, extended surface area, relatively moderate strength, easier desorption, and thermal stability [12].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, different types of adsorbents have been used in CO 2 PSA, such as zeolites, activated carbons, silica gel, metal-organic frameworks (MOFs), and porous organic polymers [10][11][12][13][14][15]. Activated carbons generally have higher CO 2 adsorption capacity than zeolite-like materials at pressures greater than atmospheric pressure due to surface hydrophobicity, extended surface area, relatively moderate strength, easier desorption, and thermal stability [12].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Zeolites, mesoporous silica, and MOFs show negligible CO 2 adsorption at 300°C due to their surface chemistry and structural instability. Nanoporous carbon as a non-oxide porous material has great scientific and technological applications in CO 2 adsorption.…”
Section: -4mentioning
confidence: 99%
“…Till date, however, metal complexes of those porous organic polymers are either created by the introduction of metal ions via post-functionalization [58], or by the use of predefined metal phthalocyanine [59] or porphyrin [60] building blocks as reactants. In 2012, Modak et al [61] reported a series of iron-containing porous organic polymers (Fe-POPs) through a simple one-pot bottom-up approach involving extended aromatic substitution on pyrrole with aromatic dialdehydes. The Fe-POPs possess high BET surface area (875 m 2 g −1 ) and large micropores and showed excellent CO 2 capture (~19 wt%) at 273 K/1 bar.…”
Section: Covalent Organic Frameworkmentioning
confidence: 99%